Effects of chronic experimental alcoholism on the epithelium of the uterine horn of rats (Rattus norvegicus albinus) - Martinez, Marcelo; Garcia, P. J.; Cagnon, V. H. A.; Mello Júnior, Wílson de [UNESP]; Padovani, C. R.; Martinez, F. E. (My University, 2001)
Sixty adult tats (Rattus norvegicus albinus) of the same age (3 months) and with a mean body weight of 228 g were divided into two experimental groups. The control group received solid diet (Purina rat chow) and tap water ad libitum. The other (alcoholic group), received the same solid diet and was allowed to drink only sugar cane brandy dissolved in 30° Gay Lussac (v/v). At the end of periods of 90, 180 and 270 days of treatment, the animals were anaesthetized with ethyl ether during estrus, weighed and sacrificed. The final mean body weights were similar in the control and alcoholic groups. The results showed intense atrophy on the lining epithelium of the endometrium of uterine horns in the alcoholic group. Important ultrastructural epithelial alterations were also observed in the female alcoholic group, such as: intense lipid droplet accumulation, increased rough endoplasmic reticulum cisternae and mitochondrial size and presence of intraepithelial neutrophils. The secretory activity of these rats was reduced. Therefore, we concluded that alcohol acts as a toxin on the epithelial layer of the rat endometrium.
Keywords: Alcoholism; Epithelium; Rats; Uterine horns; alcoholic beverage; alcoholism; animal; atrophy; body weight; cell organelle; chemically induced disorder; disease model; drug effect; electron microscopy; epithelium; female; pathology; rat; rat strain; time; ultrastructure; uterus; Alcoholic Beverages; Animals; Atrophy; Body Weight; Disease Models, Animal; Female; Microscopy, Electron; Organelles; Rats, Inbred Strains; Time Factors; Uterus